Comportamiento agronómico del cultivo de pimiento (Capsicum annuum) con diferentes abonos orgánicos en la finca experimental La María UTEQ, año 2014 - Guamangallo Alvarado, Jos Luis (2015)
This research was conducted at the Experimental Farm La Maria property UTEQ. Which is located at km 7 1/2 via the Empalme Quevedo, province of Los Rios, geographic location coordinates, length and 1° 02’ 24’’ west longitude 70° 26’ 26’’. The investigation lasted 120 days. Organic fertilization was evaluated in the production of pepper (Capsicum annunm) applied to the soil with seven different treatments, four replicates per treatment. The best result was the T3 (5kg / hl) of vermicompost production reaching 58,12kg, with 1.30% on cost benefit, while the lower profitability was the T7 (44.2 kg) treatment that is 0.71%. For comparison between treatments. Tukey's test at 5% probability was used, the study variables were plant height, stem length, length and width of fruit, fruit number and fruit yield. Statistical analysis showed statistical difference in the variable length of stem between 15 and 45 days in the width of the product and performance. The increased presence of fruit was in Q3 (5kg / hl) humus with sweet peppers 830 treatment.